Inspection and repair of concrete and masonry in marine and waterway structures delegate information : 26 April 2001 (Thomas Telford, 2001)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a seminar held at Liverpool University 26 April 2001.